Peran Pemerintah dalam Pengembangan Wisata Romokalisari Kecamatan Benowo Kota Surabaya - Via Irma Puji Dayanti; Rachmawati Novaria; Adi Soesiantoro (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research examines the role of the government in developing Romokalisari tourism in Surabaya, the importance of motivation and encouragement from the government in this effort. The research found that there are several obstacles faced, including difficulty involving the community in organized training, lack of adequate facilities, and the need for infrastructure improvements. The government has taken initiatives through outreach and training as part of its development strategy, but still faces challenges in actively involving the community. In addition, improving facilities and promoting tourism is considered important to attract more tourists. This research recommends increasing community motivation to participate more actively, improving existing facilities, and encouraging close collaboration between the government and local communities. Further synergy between the government and the community is needed to achieve sustainable and competitive tourism development in Romokalisari.